Successful Management of Teeth with Different Types of Endodontic-Periodontal Lesions - Hind Alquthami; Abdulaziz M. Almalik; Faisal F. Alzahrani; Lana Badawi (Case Reports in Dentistry)
Endodontic-periodontal diseases often present great challenges to the clinician in their diagnosis, management, and prognosis. Understanding the disease process through cause-and-effect relationships between the pulp and supporting periodontal tissues with the aid of rational classifications leads to successful treatment outcomes. In this report, we present several treatment modalities in patients with different endodontic-periodontal lesions. A modification to the new endodontic-periodontic classification, Al-Fouzan’s classification, was also added. The first case was classified as retrograde periodontal disease (i.e., primary endodontic lesion with drainage through the periodontal ligament). The second case was diagnosed as an iatrogenic periodontal lesion caused by root perforation. The third case was diagnosed as an iatrogenic periodontal lesion caused by tooth trauma due to orthodontic treatment. The first two cases were managed with a nonsurgical approach, whereas the third case was managed with nonsurgical and surgical approaches. All patients showed complete healing of soft and hard tissue lesions. A thorough understanding of the disease history and the patient’s signs and symptoms, complete examination with full investigation, and the use of a systematic step-by-step approach in the management of such challenging endodontic-periodontal lesions with regular recall visits were very useful and successful.